2017
DOI: 10.2217/fon-2017-0178
|View full text |Cite
|
Sign up to set email alerts
|

The expression profile and clinicopathological significance of Notch1 in patients with colorectal cancer: a meta-analysis

Abstract: Notch1 overexpression in CRC suggested aggressive biological behaviors and thus implying that Notch1 may be a useful biomarker in CRCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Previous evidence has demonstrated that activated Notch signaling is maintained throughout CRC tumorigenesis (25). In addition, enhanced levels of Notch-1 have been associated with progression, tumor grade and metastasis (26). Using the miRNA target prediction programs, we found that the 3'-UTRs of Notch-1 mRNAs contain conserved miR-449a binding sites, which are highly conserved among human, mouse, rat, chimpanzee, dog and chicken species (Fig.…”
Section: Mir-449a Inhibits Cac Growth and Invasion By Targetingmentioning
confidence: 77%
“…Previous evidence has demonstrated that activated Notch signaling is maintained throughout CRC tumorigenesis (25). In addition, enhanced levels of Notch-1 have been associated with progression, tumor grade and metastasis (26). Using the miRNA target prediction programs, we found that the 3'-UTRs of Notch-1 mRNAs contain conserved miR-449a binding sites, which are highly conserved among human, mouse, rat, chimpanzee, dog and chicken species (Fig.…”
Section: Mir-449a Inhibits Cac Growth and Invasion By Targetingmentioning
confidence: 77%
“…Notch is a contributory factor for various cancers. [ 14 ] Notch1 is increased in human breast, [ 15 ] colorectal, [ 16 ] esophageal cancer, [ 17 ] pancreatic, [ 18 ] and prostate cancers. [ 19 ] For instance, miR‐139‐5p sensitizes CRC cells to 5‐fluorouracil by targeting Notch‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Notch 3 is overexpressed in a subset of colorectal cancer patients and induction of Notch 3 overexpression in colorectal cancer xenografts led to increased tumour formation [ 84 ]. A meta-analysis of 13 studies, including 3401 patients, reported a significant association between Notch 1 expression and colorectal cancer samples compared to noncancerous normal tissues, and clinical parameters were indicative of colorectal cancer invasion and metastasis (e.g., lymph node metastasis and depth of tumour infiltration in the surrounding tissue) [ 85 ].…”
Section: Notch In Cancer: An Overviewmentioning
confidence: 99%